Implementation of sustainable development goals at the local-neighborhood scale - Alonso Frank, Alción de Las Pléyades (2023)
The 2030 Agenda for Sustainable Development Goals (SDGs) establishes global goals from an action plan at various scales on south of Latin-American. However, it is necessary to facilitate cooperation between actors, agendas, and urban policies at the local-neighborhood level to enable the progressive transformation that the Agenda projects. The objective of this paper is to propose a methodology that translates these SDGs to the local-neighborhood scale and apply it to "Barrio Virgen de Lourdes", located in San Juan province, Argentina. The study was carried out in a participatory manner, in conjunction with community, academic, and governmental actors. As a result, Urban Sustainability Indicators and action strategies according to neighborhood SDGs were obtained. In addition, a Sustainable Development Index was designed to assess the impact of actions on the realization of the SDGs at different levels of government. This methodology represents an effective tool to contribute to sustainable development and social inclusion.